Isaiah 40-66: translation and commentary - Paul, Shalom M. (The Eerdmans Critical Commentary, 2012)
Intro -- Title Page -- Copyright -- Dedication -- Contents -- Preface -- Abbreviations -- Introduction -- 1. Deutero-Isaiah -- 2. Trito-Isaiah? -- 3. Historical Survey -- Excursus A: Prayer of Nabonidus -- Excursus B: Cyrus Cylinder -- 4. Rishonôt and Ḥadashôt -- 5. Servant Songs -- 6. Attitudes toward Foreigners and Religious Universalism -- 7. Deutero-Isaiah, Polemicist -- 8. Descriptions of Jerusalem -- 9. Descriptions of God, His Attributes, and His Relationship to His People -- 10. Unique Style and Literary Sequence -- 11. Language of the Book: Aramaic and Late Hebrew -- 12. Inner-Biblical Traditions Reflected in Deutero-Isaiah -- 13. Deuteronomic and Deuteronomistic Influences on Deutero-Isaiah -- 14. Influence of First Isaiah on Deutero-Isaiah -- 15. Influence of Jeremiah on Deutero-Isaiah -- 16. Additional Prophetic Influences on Deutero-Isaiah -- 17. Psalmic Influences on Deutero-Isaiah -- 18. Parallels between the Book of Lamentations and Deutero-Isaiah -- 19. Deutero-Isaiah and the Literary Heritage of the Ancient Near East -- 20. Isaiah Scrolls from Qumran and Ancient Translations -- 21. Deutero-Isaiah in Jewish Liturgy -- Translation -- Commentary -- Chapter 41 -- Chapter 42 -- Chapter 43 -- Chapter 44 -- Chapter 45 -- Chapter 46 -- Chapter 47 -- Chapter 48 -- Chapter 49 -- Chapter 50 -- Chapter 51 -- Chapter 52 -- 52:13-53:12 -- Chapter 54 -- Chapter 55 -- Chapter 56 -- Chapter 57 -- Chapter 58 -- Chapter 59 -- Chapter 60 -- Chapter 61 -- Chapter 62 -- Chapter 63 -- Chapter 64 -- Chapter 65 -- Chapter 66 -- Selected Bibliography -- Index of Authors -- Index of Subjects -- Literary Devices -- Scribal Phenomena -- Index of Sources -- Index of Commentaries on Isaiah.